STRUCTURAL AND SEMANTIC ANALYSIS OF SOMATIC HYBRID PROVERBS IN ENGLISH - Turdaliyeva Shahnoza O‘ktamovna (Bright Mind Publishing, 2025)
This paper analyzes English proverbs that involve two or more body parts—so-called somatic hybrid proverbs—from both structural and semantic perspectives. These expressions, such as “keep your eyes and ears open” or “put your heart and soul into it,” carry metaphorical and culturally rich meanings. The article categorizes their syntactic structures, examines the semantic roles of the body parts, and explores their figurative implications in everyday English discourse. Findings suggest that somatic proverbs are highly symbolic, often encoding cultural values, emotional states, and social behaviors through the metaphorical use of body parts . Structurally, they follow patterns such as parallel constructions, coordinated noun phrases, and imperative or declarative syntactic frames. Semantically, they convey a wide range of pragmatic functions—warnings, encouragements, moral lessons, or behavioral prescriptions . These proverbs also highlight the cognitive embodiment of abstract concepts . This study contributes to the understanding of figurative language in English and provides comparative insights for further paremiological studies, particularly in cross-cultural and bilingual contexts.
Keywords: Somatic proverbs, hybrid idioms, structural-semantic analysis, English language, metaphor, body parts, connotation.